Digital Sonar Design in Underwater Acoustics Principles and Applications - Li, Qihu.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
"Digital Sonar Design in Underwater Acoustics Principles and Applications" provides comprehensive and up-to-date coverage of research on sonar design, including the basic theory and techniques of digital signal processing, basic concept of information theory, ocean acoustics, underwater acoustic signal propagation theory, and underwater signal processing theory. This book discusses the general design procedure and approaches to implementation, the design method, system simulation theory and techniques, sonar tests in the laboratory, lake and sea, and practical validation criteria and methods for digital sonar design. It is intended for researchers in the fields of underwater signal processing and sonar design, and also for navy officers and ocean explorers. Qihu Li is a professor at the Institute of Acoustics, Chinese Academy of Sciences, and an academician of the Chinese Academy of Sciences.
Brief history of digital sonar development -- Basic theory of digital signal processing -- Detection and estimation theory of digital signal -- General principle of sonar design -- Design of digital sonar -- The implementation method of various function of digital sonar -- System simulation technique in digital sonar design -- Examples of typical modern digital sonar.-Software and hardware support and performance evaluation in digital sonar design.
Keywords: Physics; Physical geography; Oceanography; Acoustics; Computer engineering; Physics; Acoustics; Electrical Engineering; Oceanography; Geophysics/Geodesy.